Moderating Multiple Mediation Model of the Impact of Inclusive Leadership on Employee Innovative Behavior - Wang, Hui; Chen, Min; Li, Xiangqing (Frontiers in Psychology, 2021)
Leadership is an important antecedent variable of employee innovative behavior. Previous studies on the influence of inclusive leadership on employee innovative behavior mostly focused on the single mediating variable, which may lead to parameter estimation deviation due to the omission of other mediating variables. According to the social cognitive theory and motivation theory, and from the perspective of cognitive-motivation integration, this study established a moderating multiple mediation model to understand the impact of inclusive leadership on employee innovative behavior, which used psychological safety and creative self-efficacy as mediating variables and innovation rewards as moderating variables. Data was collected from 418 employees of manufacturing industry in China. Consistent with our hypotheses, the results show that, first, inclusive leadership positively effect on employee innovative behavior. Second, psychological safety and creative self-efficacy both play a part mediating effect between inclusive leadership and employee innovative behavior, and the mediating effect of psychological safety is significantly smaller than that of creative self-efficacy. Third, innovation rewards positively moderates relationship of "psychological safety--employee innovative behavior" and relationship of "self-efficacy--employee innovative behavior". Fourth, innovation rewards positively moderates the indirect effect of inclusive leadership on employee innovative behavior through psychological safety and creative self-efficacy. These findings not only helpful to expand the influence mechanism of inclusive leadership on employee innovative behavior, but also provided some suggestions for enterprise innovation development.